Application of I-BOS System as Financial Reporting of BOS at SDN Sukanagara - Erick Febriyanto; Qurotul Aini; Aa Mustopa (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
The School operational Assistance (BOS) is a government program for the provision of cost financing for basic education units as compulsory learning program executor. The particular purpose is to relieve the levy to relieve the burden of students. All schools are already listed in primary and secondary education principal data system. School is the most important element in determining the use of BOS funds because it is directly related to management. Based on the provisions applicable in the the Office of the BOS year 2012 BOS fund managed by the principal with the teacher or administrative personnel appointed as Treasurer. The current financial information on the world of education in which the data input collection is very complicated in the system of the process is very effective and efficient, in order to see data on the purchase or expense after that the Treasurer must Check back the statement of purchase and expense papers on the bank and all the reports of the paper have been made by the current Treasurer can be easily accessed by the leadership, one of which is presenting information using tables and in The workmanship system requires very high accuracy to ensure that any nominal information of money included in the table has to be ensured the truth is very less efficient. In order to facilitate the Treasurer in the recording of financial statements and leaders who perform a reduction in the information presented at SDN Sukanagara.